2008
DOI: 10.1111/j.1471-0528.2007.01576.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of a decision aid for prenatal testing of fetal abnormalities to improve women’s informed decision making: a cluster randomised controlled trial [ISRCTN22532458]

Abstract: Objective To evaluate the effectiveness of a decision aid for prenatal testing of fetal abnormalities compared with a pamphlet in supporting women's decision making.Design A cluster randomised controlled trial.Setting Primary health care.Population Women in early pregnancy consulting a GP.Methods GPs were randomised to provide women with either a decision aid or a pamphlet. The decision aid was a 24-page booklet designed using the Ottowa Decision Framework. The pamphlet was an existing resource available in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
134
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(142 citation statements)
references
References 46 publications
7
134
1
Order By: Relevance
“…11,13,26,[28][29][30][31][32][33][34][35] Twenty-two studies were prospective, 12,28,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] including cross-sectional, 41,42,49 quasi-experimental, 53 pilot, 50 and longitudinal study designs. 52 Of the RCTs, five involved an information or educational intervention, 28,29,[32][33][34] five randomised the screening offer, 11,13,26,30,35 and there was one decision aid trial.…”
Section: Summary Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…11,13,26,[28][29][30][31][32][33][34][35] Twenty-two studies were prospective, 12,28,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] including cross-sectional, 41,42,49 quasi-experimental, 53 pilot, 50 and longitudinal study designs. 52 Of the RCTs, five involved an information or educational intervention, 28,29,[32][33][34] five randomised the screening offer, 11,13,26,30,35 and there was one decision aid trial.…”
Section: Summary Of Studiesmentioning
confidence: 99%
“…52 Of the RCTs, five involved an information or educational intervention, 28,29,[32][33][34] five randomised the screening offer, 11,13,26,30,35 and there was one decision aid trial. 31 The 33 studies were published between 1991, 54 and 2012, 36 with 25 studies published between 2002 and 2012. Three studies used the same cohort as in previous studies; 13,39,46 in subsequent studies the sample was stratified differently, 40 different measures were applied, 11 and additional validation data were reported.…”
Section: Summary Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…[10][11][12][13] Use of decision aids for prenatal counseling using structured, paper-based or basic electronic tools has been associated with less decision conflict, improved knowledge, and in some cases, increased uptake of prenatal testing. [14][15][16][17][18] Such tools can facilitate an improved informed consent process, yet few decision aids have been developed and evaluated in the United States, particularly for use in low literacy populations. 11 In 2009, Kuppermann et al showed that use of an interactive prenatal diagnostic decision tool resulted in better patient satisfaction, more decision certainty, and more accurate estimates of risk among women receiving prenatal genetic counseling.…”
Section: Introductionmentioning
confidence: 99%